2020
DOI: 10.1080/21645515.2020.1711678
|View full text |Cite
|
Sign up to set email alerts
|

Short-term dynamic changes in neutralizing antibodies against enterovirus 71 after vaccination

Abstract: Background: Short-term dynamic changes in neutralizing antibodies against EV71 and EV71-IgM after inactivated EV71 vaccine injection are unknown. Methods: This study was designed as a randomized, open-label study and was registered at ClinicalTrials.gov (NCT03278132). In total, 120 healthy infants aged 6-35 months were randomized 1:1:1 to provide a second blood sample on day 10, day 20, or day 30 after the first vaccine dose, respectively. Results: According to the per-protocol set, a rapid immune response aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…It was suggested that pre-immunization blocks EV71 infection, which is due to the previous effect of IgM produced by EV71 vaccine-induced mice ( 37 ). As indicated from recent clinical trials of the EV71 vaccine, it can be used for emergency vaccination for anti-EV71 infection ( 38 ). At present, the CVA6 vaccine has not been used clinically, so it is necessary to clarify the type of antibodies induced by the CVA6 vaccine and the level of neutralizing antibodies and its changes, for the early prevention of CVA6 infection.…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that pre-immunization blocks EV71 infection, which is due to the previous effect of IgM produced by EV71 vaccine-induced mice ( 37 ). As indicated from recent clinical trials of the EV71 vaccine, it can be used for emergency vaccination for anti-EV71 infection ( 38 ). At present, the CVA6 vaccine has not been used clinically, so it is necessary to clarify the type of antibodies induced by the CVA6 vaccine and the level of neutralizing antibodies and its changes, for the early prevention of CVA6 infection.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, EV71 is the main virus strain causing HFMD in infants. 3 Therefore, it is highly infectious and can infect the central nervous system, posing a serious threat to public health. 4 At present, the main drugs used in clinical drug treatments, such as ribavirin and oseltamivir, have limited therapeutic effects and toxic side effects 5,6 .…”
Section: Introductionmentioning
confidence: 99%
“…It can combine with appropriate compounds to stabilize the viral capsid and prevent the un‐coating of virus and release of RNA. Indeed, EV71 is the main virus strain causing HFMD in infants 3 . Therefore, it is highly infectious and can infect the central nervous system, posing a serious threat to public health 4 .…”
Section: Introductionmentioning
confidence: 99%